2022
DOI: 10.1016/j.paid.2022.111524
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators of willingness to vaccinate against COVID-19: Role of prosociality, authoritarianism and conspiracy mentality. A four-wave longitudinal study

Abstract: Aim We investigated longitudinal relations between individual willingness to undergo vaccination against COVID-19 and three social factors: conspiracy mentality, prosociality, and authoritarianism. Method This longitudinal study comprised four measurement points. The first wave sample included 1130 responses and was representative of the Polish population in terms of gender, age, and place of residence. Analyses were performed using random intercept cross-lagged panel m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 97 publications
2
15
0
2
Order By: Relevance
“… Kachurka et al (2021) found that nearly 45% of the Polish respondents were unwilling to be vaccinated, and none of the popular messages we used was effective in reducing this hesitancy ( Kachurka, Krawczyk, & Rachubik, 2021 ). Some studies have demonstrated that anti-vaccine attitudes are related to anti-establishment attitudes and reflect the political polarization in Poland ( Oleksy, et al, 2022 ). Moreover, believe in conspiracy theories seem to be common among Polish and, thus, one of the most important factors reducing willingness to undergo vaccination ( Sowa, et al, 2021 ).The high vaccination hesitancy observed in Poland might be reflected in the attitudes among those Polish immigrants in Norway who mostly follow Polish media.…”
Section: Discussionmentioning
confidence: 99%
“… Kachurka et al (2021) found that nearly 45% of the Polish respondents were unwilling to be vaccinated, and none of the popular messages we used was effective in reducing this hesitancy ( Kachurka, Krawczyk, & Rachubik, 2021 ). Some studies have demonstrated that anti-vaccine attitudes are related to anti-establishment attitudes and reflect the political polarization in Poland ( Oleksy, et al, 2022 ). Moreover, believe in conspiracy theories seem to be common among Polish and, thus, one of the most important factors reducing willingness to undergo vaccination ( Sowa, et al, 2021 ).The high vaccination hesitancy observed in Poland might be reflected in the attitudes among those Polish immigrants in Norway who mostly follow Polish media.…”
Section: Discussionmentioning
confidence: 99%
“…Older people are concerned about inadequate vaccination of the population and the resulting lack of herd immunity. Other Polish studies show that age is an important variable when it comes to vaccination willingness e.g., Babicki and Mastalerz-Migas [ 16 ], Raciborski and co. [ 17 ] and Oleksy and co. [ 25 ]. Since the beginning of the pandemic, the media have been reporting new cases worldwide, with an emphasis on the severity of disease symptoms and high mortality rates in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth emphasizing that changes in the level of acceptance of vaccines have been observed over time. A study by Oleksy and co. [ 25 ] shows that willingness to be vaccinated against COVID-19 continued to decrease with each successive wave of the pandemic: the highest willingness to get vaccinated was declared by respondents during the first wave and the lowest during the fourth wave.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mixed findings also extend to attitudes toward COVID-19 vaccination. Across different contexts, RWA has been shown to have positive ( Bilewicz & Soral, 2021 ), negative ( Oleksy et al, 2022 ), or mixed ( Murphy et al, 2021 ) relationships with COVID-19 vaccine acceptance. Some research has also shown that RWA predicts skepticism toward vaccination in general ( Kempthorne & Terrizzi, 2021 ).…”
Section: Introductionmentioning
confidence: 99%